Machalilla revisited - New data for the Early Formative Period of Coastal Ecuador - Prümers, Heiko; Ugalde, Fernanda; Dyrdahl, Eric (Journal of Global Archaeology, 2023)
In 2017, the German Archaeological Institute (DAI) initiated a joint project with the Pontificia Universidad Católica del Ecuador, Quito (PUCE), to study the Machalilla culture, a cultural expression from the Ecuadorian coast that belongs to the Formative Period (4400 – 300 cal BC). Here we present the results of our excavations at the type-site with a focus on the presentation of the finds as well as their chronological classification. The data presented here include the first radiocarbon dates for the type-site, help refine our understanding of the material culture related to Machalilla, and confirm Estrada´s estimation that the site is single component and that its occupation dates back to the early period of the Machalilla culture.